High HCV seroprevalence and HIV drug use risk behaviors among injection drug users in Pakistan - Zafar Tariq; Thomas David L; Galai Noya; ul-Hasan Salman; Kuo Irene; Ahmed Mohammad A; Strathdee Steffanie A (BMC, 2006)
Abstract Introduction HIV and HCV risk behaviors among injection drug users (IDUs) in two urban areas in Pakistan were identified. Methods From May to June 2003, 351 IDUs recruited in harm-reduction drop-in centers operated by a national non-governmental organization in Lahore (Punjab province) and Quetta (Balochistan province) completed an interviewer-administered survey and were tested for HIV and HCV. Multivariable logistic regression identified correlates of seropositivity, stratifying by site. All study participants provided written, informed consent. Results All but two were male; median age was 35 and <50% had any formal education. None were HIV-positive; HCV seroprevalence was 88%. HIV awareness was relatively high, but HCV awareness was low (19%). Injection behaviors and percutaneous exposures such as drawing blood into a syringe while injecting ('jerking'), longer duration of injection, and receiving a street barber shave were significantly associated with HCV seropositivity. Discussion Despite no HIV cases, overall HCV prevalence was very high, signaling the potential for a future HIV epidemic among IDUs across Pakistan. Programs to increase needle exchange, drug treatment and HIV and HCV awareness should be implemented immediately.